Desain Interior Pusat Seni Pertunjukan Berbasis Nilai Budaya Jawa di Surakarta - Shintia Dewi Limanto; Laksmi Kusuma Wardani; Stephanie Melinda Frans (Intra, 2018)
Performing art is a work of art that involves several individuals or a group in particular place and time. Surakarta is known as a cultural city that has various performing arts that are quite popular, such as karawitan art, puppetry art, dance art, and theater art. The potential of art possessed by Surakarta is supported by communities engaged in performing arts. However, the performing arts have not been well facilitated so that people are less interested in seeing the show at the facilities that have been provided. Considering those facts, this design is intended to provide adequate facilities to support the performing art activities in Surakarta. The design of this facility is intended to give a supportive place for every activity of performing arts with local cultural values concept. This concept will make performing art easily accepted by the community, or in this case Javanese people. Application of this design will be applying the character of the puppet that is Pandavas which is implemented with the concept of Java house that is rasmi, hita, apik, asri. With this concept of Javanese local cultural values, this design is expected to be easily accepted by the public.